The effect of organobentonites from spent bleaching earth (SBE) and commercial bentonite on nanocomposite properties - Paramith, Tika; P Sitompul, Johnner; Woo Lee, Hyung (International Journal of Engineering and Technology, 2018)
This paper concerns on synthesis of nanocomposites consisting of Poly(lactic acid) (PLA) and clays. Two types of clays were regenerated organobentonite and commercial organobentonite. PLA and clays were melt extruded using single-screw extruder. The extruded compound was pelletized, then hot pressed using compression molding machine. Regenerated organobentonite was obtained from regeneration of spent bleaching earth (SBE) using solvent extraction and oxidation method. Afterwards, regenerated SBE modified by organic compound. While, commercial organobentonite was directly modified of commercial bentonite using organic compound. In this study, nanocomposites were prepared with varying compositions of clays from 0% to 5% (by weight). Experimental results show that partially exfoliated nanocomposites structure was shown by X-ray diffraction analyses. In addition, the effect of clays on morphology structure, mechanical, barrier, and biodegradable properties were analyzed. The utilization of clays in nanocomposite increases mechanical properties at low clay compositions. Furthermore, PLA-clay nanocomposites show better barrier and biodegradable properties compared to that of the neat PLA.Â Â